Metapoetic Metaphor in Georgy Shengeli’s Poetry and Prose - Rogacheva, Natalya (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article deals with the semantics of metapoetic term and metapoetic metaphor in the artistic and academic discourse of Georgy Shengeli, poet and versification expert. The paper scrutinizes a complex of metaphors used by Shengeli in his theoretical and lyrical texts to define rhythm, rhyme, stanza, and other poetological categories. A thematic classification of such metaphoric labels is proposed (military, architectural, physiologic and other metaphors of a poetic text). An analysis of the metaphor of breath in Shengeli’s poems and research texts reveals similarities and differences in shaping figurative meanings in the artistic and the academic context.